Analysis of Waste Water Treatment plant to enhance the Eco-friendly Environment using Data Mining Techniques - V, Meghana.; Bai.B.G, Mamatha; Majum, Jharna; ., . (International Journal of Engineering and Technology, 2018)
E-commerce is one of the rapidly booming sectors in India today, thanks to the rising internet user base and faster mobile penetration.Â  The E-commerce industry is a complex ecosystem as it involves huge transaction volumes, complex procurement and logistics systems and reliance on new technologies for customer access and payment transactions. This complexity has given rise to frauds and revenue leakages which is impacting the revenue for the ecommerce companies. Hence the major concern facing the Ecommerce sector today is how to mitigate the revenue loss. Very few studies have been done in academic literature in this area hence the objective of this study is to understand the sources of revenue leakage in the ecommerce sector and propose solutions for mitigating these revenue leakages. The study focuses on 2 major areas of revenue leakage viz. Customer side, Vendor side. The proposed revenue assurance model will be helpful to Ecommerce companies for detecting the sources of revenue leakages in the abovementioned areas and plugging the same thereby reducing losses. The study can also be helpful for consulting companies who are in the business of revenue assurance and fraud management for the ecommerce companies.Â Â
Keywords: Data Mining; Waste Water Treatment Plant; G-means; CLARA; DBSCAN